Serum Occludin Level Combined With NIHSS Score Predicts Hemorrhage Transformation in Ischemic Stroke Patients With Reperfusion - Yuan, Shuhua; Li, Weili; Hou, Chengbei; Kang, Huining; Ma, Qingfeng; Ji, Xunming; Qi, Zhifeng; Liu, Ke Jian (Frontiers in Cellular Neuroscience, 2021)
Hemorrhagic transformation (HT) is one of common complications for acute ischemic stroke or after interventions, leading to poor prognosis. Serum occludin level is related with blood brain barrier disruption and National Institute of Health stroke scale (NIHSS) score reflects stroke severity. We aimed to investigate whether the two covariates are independently associated with HT and their combination can improve the accuracy of HT prediction in ischemic stroke patients with reperfusion therapy. Seventy-six patients were screened from the established database of acute ischemic stroke in our previous study, which contains all clinical information, including serum occludin levels, baseline NIHSS score and hemorrhagic events. Multivariate logistic regression analysis showed that serum occludin level (OR=4.969, 95%CI: 2.069-11.935, p<0.001) and baseline NIHSS score (OR=1.293, 95%CI: 1.079-1.550, p=0.005) were independent risk factors of HT after adjusting for potential confounders. Compared with non-HT patients, HT patients had higher baseline NIHSS score [12 (10.5-18.0) versus 6 (4-12), p=0.003] and serum occludin level (5.47±1.25 versus 3.81±1.19, p<0.001). Moreover, ROC curve based on leave-one-out cross-validation showed that the combination of serum occludin level and NIHSS score significantly improved the accuracy of predicting HT (0.928, 95%CI：0.871-0.986，p<0.001). These findings suggest that the combination of two methods can provide a better tool for HT prediction in acute ischemic stroke patients with reperfusion therapy.